Одномоментне протезування дефектів постійних зубів у дітей-інвалідів під загальним знеболенням у період змінного прикусу - Гавриленко, Марина Аркадіївна; Gavrilenko, M. A. (My University, 2014)
Мета: використання загального знеболення при протезуванні дефектів перших постійних молярів у дітей-інвалідів у період змінного прикусу. Матеріали та методи дослідження. У дослідженні взяли участь 44 дитини-інваліди віком від 7 до 12-ти років, яких комплексно обстежили стоматологи. Під загальним знеболенням проведена санація порожнини рота й відновлено дефект коронки перших постійних молярів. Вибір конструкції та методу відновлення залежав від стану пульпи, ступеня сформованості коренів і розмірів дефекту. Результати. У більшості обстежених дітей спостерігались дефекти твердих тканин постійних молярів більше 2/3. Як найбільш ефективне слід відмітити одномоментне протезування перманентними акриловими коронками перших постійних молярів, що потребували довготривалого ендодонтичного лікування. Лікування проводили від загальним знеболенням. Висновок. Отже, у постійних зубах дітей-інвалідів при значних дефектах і необхідності довгострокового ендодонтичного лікування можна використовувати тимчасові ортопедичні методи лікування під загальним знеболенням. Така тактика дозволяє створити умови для завершення росту постійних зубів і щелеп у дітей-інвалідів у період змінного прикусу і є профілактикою передчасного видалення постійних зубів і зубощелепної патології. Aim: the use of general anesthesia in prosthetics of defects of the first permanent molars in disabled children during the period of mixed dentition. Materials and methods of the research. The study involved 44 disabled children aged from 7 to 12 years old, who underwent the comprehensive dental examination. Under general anesthesia sanitation of the oral cavity was performed and defect of the crown of the first permanent molars was restored. The choice of construction and method of restoration depended on the state of the pulp, degree of the formedness of roots and size of the defect. Results. The majority of the examined children had hard tissue defects of permanent molars more than 2/3. The most effective prosthetics was the simultaneous one using permanent acrylic crowns for the first permanent molars requiring long endodontic treatment. Treatment was performed under general anesthesia. Conclusion. Thus in disabled children in permanent teeth with major defects and in need of long-term endodontic treatment it is possible to use temporary orthopedic methods of treatment under general anesthesia. Such tactics will allow creating conditions for the end of growth of permanent teeth and jaws in disabled children during the period of mixed dentition and it is the prevention of premature removal of permanent teeth and dentoalveolar pathology.
Simultaneously prosthetics defects permanent teeth in children-invalids under general anesthesia during mixed dentition
Keywords: діти-інваліди; загальне знеболення; дефекти постійних зубів; disabled children; general anesthesia; defects of permanent teeth